Muslim Minority Identity in Western Societies: A Systematic Review and Bibliometric Analysis - Anis Khoirunnisa Syahrussalamah; Muhammad Nurfazri; Hadela Yuri Nuraprilianti; Dody S. Truna; Erni Haryanti; Afita Nur Hayati; Endah Nur Latifah (KEDJATI Journal of Islamic Civilization, 2025)
This study systematically maps scholarly research on the cultural and identity negotiation of Muslim minorities in Western societies through a systematic literature review and bibliometric analysis of the Scopus database published between 2004 and 2024. From an initial corpus of 213 records, 22 articles met the inclusion criteria and formed the analytical dataset. The results demonstrate that research on Muslim minority identity constitutes a sustained and significant field of inquiry, with publication trends showing steady growth, particularly after 2018, in response to evolving socio-political conditions in Western contexts. Besides, bibliometric mapping reveals that current research is structured around five dominant thematic clusters: identity negotiation, integration and national belonging, gender and intersectionality, media and representation, and transnational memory and diaspora. High-frequency keywords such as identity, Islam, Europe, cultural identity, religion, and immigrant indicate a strong conceptual emphasis on identity as a relational and contested construct. The findings further show that Muslim minority identity is predominantly theorized as a dynamic process shaped by interactions among state policies, educational institutions, media discourses, everyday religious practices, and collective memory, rather than through fixed or assimilationist models. Theoretically, these patterns reinforce frameworks of diasporic identity and cultural hybridity. Practically, they highlight the need for interdisciplinary approaches that integrate religious studies, sociology, media studies, and education. By empirically situating religion as a lived and socially negotiated practice, this study advances religious studies. Hence, it provides a foundation for future research on religion, identity, and power in plural societies.